Seasonal influence on volatile aroma constituents of two banana cultivars (Grand Naine and Nendran) under Kerala conditions - Shivashankara K S (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2017)
Banana is a tropical fruit with a pleasant flavour, widely consumed throughout the world. Volatile aroma compounds are responsible for olfactory flavor of banana. However, the development of aroma flavors is affected by the atmospheric temperatures during fruit growth period. In order to get good quality fruits in terms of aroma it is essential to understand the optimum temperature for maximum aroma production. The approach used in this study was to alter the dates of harvest to understand the optimum temperature required for maximum production of volatile compounds under Kerala conditions. The results revealed that with increased temperature volatile aroma compounds decreased in cvs. Grand Naine and Nendran. Total volatile compounds were higher in cv. Grand Naine compared to cv. Nendran. Cultivar Nendran recorded increased concentrations of esters, alcohols and decreased aldehydes, ketones, hydrocarbons and acids at high temperatures. Phenols and other constituents did not show much variation with respect to the temperature variation in both the cultivars. Among esters, Isoamyl butanoate and 3-Methylbutyl-3-methylbutyrate esters were the most abundant in both the cultivars. Ketones, especially 4-Methyl-1-penten-3-one was higher in cv. Nendran whereas esters were lower compared to cv. Grand Naine. Total area of aroma constituents in cultivars Grand Naine and Nendran were high in October followed by February with mean atmospheric temperature of 30.5ºC and 32.6ºC respectively. In case of cv. Nendran, total area of esters and alcohols were maximum at high temperature (34.5ºC) but in cv. Grand Naine, esters and alcohols decreased with high temperature. Results indicated that fruits harvested in October were better in terms of volatile aroma quantity in both the cultivars due to lower atmospheric temperature. Seasonal variations affected the two cultivars differentially in terms of percentage of groups of volatile compounds.